Theoretical models of learning and literacy development - Ortlieb, Evan; Cheek, Earl H. (Literacy research, practice and evaluation ;, 2014)
This book advances theoretical knowledge through rich description of cognitive and social elements of the teaching and learning processes of literacy formation. This text offers ten theories that describe how students learn in the 21st century and how to improve curriculum and instruction towards meeting the current needs of students today.